Prognostic value of targeted temperature management on outcomes of hanging-induced out-of-hospital cardiac arrest: A nationwide observational study. Issue 5 (4th February 2022) - Kim, Jae Guk; Choi, Hyun Young; Kang, Gu Hyun; Jang, Yong Soo; Kim, Wonhee; Lee, Yoonje
Abstract : Abstract: This study aimed to evaluate the prognostic significance of targeted temperature management (TTM) on hanging-induced out-of-hospital cardiac arrest (OHCA) patients using nationwide data of South Korea. Adult hanging-induced OHCA patients from 2008 to 2018 were included in this nationwide observational study. Patients who assigned into 2 groups based on whether they did (TTM group) or did not (non-TTM group) receive TTM. Outcome measures included survival to hospital discharge and a good neurological outcome at hospital discharge. Among the 293, 852 OHCA patients, 3545 patients (non-TTM, n = 2762; TTM, n = 783) were investigated. After propensity score matching for all patients, 783 matched pairs were available for analysis. We observed no significant inter-group differences in the survival to hospital discharge (non-TTM, n = 27 [3.4%] vs TTM, n = 23 [2.9%], P = .666) or good neurological outcomes (non-TTM, n = 23 [2.9%] vs TTM, n = 14 [1.8%], P = .183). In the multivariate analysis, prehospital return of spontaneous circulation (odds ratio [OR], 22.849; 95% confidence interval [CI], 11.479–45.481, P < .001) was associated with an increase in survival to hospital discharge, and age (OR, 0.971; 95% CI, 0.944–0.998, P = .035), heart disease (OR, 16.875; 95% CI, 3.028–94.036, P = .001), and prehospital return of spontaneous circulation (OR, 133.251; 95% CI, 30.512–581.930, P < .001) were significant prognostic factors of good neurological outcome. However, TTM showed no significant association with either outcome. There were no significant differences in the survival to hospital discharge and good neurological outcomes between non-TTM and TTM groups of hanging-induced OHCA patients. Abstract : Supplemental Digital Content is available in the text